The progesterone vaginal ring as luteal phase support in in vitro fertilization - Vargas-Tominaga, Luis (2022)
Objective: To compare the effectiveness of the vaginal ring and vaginal progesteronecapsules in supporting the luteal phase in in vitro fertilization procedures. Methods:Retrospective study that evaluated pregnancy outcomes in female recipients ofembryos obtained from donation of both gametes by comparing the effectivenessof the vaginal ring and vaginal progesterone capsules in supporting the luteal phasein in vitro fertilization procedures. Results: Thirty-eight women used the vaginal ringand 46 applied vaginal capsules as luteal phase support. Similar rates of implantation(36.5% versus 36.9%), clinical pregnancy (52.6% versus 50.0%) and live birth (50.0%versus 45.7%) were found. Conclusions: Similar implantation, clinical pregnancy andlive birth rates were found with the use of the vaginal ring and vaginal progesteronecapsules in the support of the luteal phase in in vitro fertilization procedures. Due tothe convenience of its use and adequate pregnancy rates, the progesterone vaginalring is an important alternative in the support of the luteal phase in in vitro fertilization.